RECURRENCE FREE SURVIVAL AND PATTERNS OF RECURRENCE IN SQUAMOUS CELL CARCINOMA OF ORAL CAVITY: AN INSTITUTIONAL PERSPECTIVE - Tariq, Muhammad; Saqib Raza Khan; Yasmin Abdul Rashid; Muhammad Nauman Zahir; Adnan Abdul Jabbar; Munira Moosajee; Samad Jehangir Shah; Sehrish Sarwar Baloch; Salman Soomar (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the recurrence-free survival (RFS) in patients with squamous cell carcinoma of oral cavity (OSCC) Methodology: It was a longitudinal study conducted on oncology patients who were diagnosed as having squamous cell carcinoma of the oral cavity and treated in our tertiary care hospital in the department of medical oncology. Patients were followed for the evaluation of disease recurrence. The Chi-square test was used to see the association between outcomes and clinicopathological features of the tumor. Results: Of 97 patients, 85(87.62%) patients had no disease, however, 12(12.37%) patients had residual/recurrent disease in the first post-treatment follow-up scans performed three months after the completion of curative treatment. Subsequent follow-up scans showed disease recurrence in 87(89.69%) patients, out of which 52 (59.77%) had loco-regional disease recurrence while 35(40.22%) patients had combined loco-regional and systemic disease recurrence with lung(n=18) being the most common site of distant metastasis. The mean RFS was 15 months (IQR= 8, 26). Patients with lymph vascular invasion (LVI), perineural invasion (PNI), positive margin, and extranodal extension(ENE) had a significantly higher risk of progressive disease after primary treatment, on follow up scans. The relationships between treatment outcomes and LVI, PNI, positive margin and ENE were statistically significant (p<0.05). Conclusion: Our study shows that there is a higher frequency of recurrence in patients with OSCC among patients with extra nodal extension, lymph vascular and perineural-invasion, and positive margins. Clinical trials are required to identify other poor prognostic factors and the need of developing a prognostic model for risk-stratification of such patients.